Comparison of traditional and fuzzy unsupervised classification on the basis of vegetation index - Havasi, István; Benő, Dávid (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
In a concise introductory part of this study the Fuzzy logic is overviewed briefly first then one of its important applications in land management, the classification is outlined. After that we deal with the theoretical membership functions well applicable to the afore- mentioned purpose and procedures taken into account here. Finally we perform a classification in the title using a concrete data set, a Landsat 7 satellite image, and the final results of this research are evaluated.
Keywords: fuzzy logic; unsupervised classification; NDVI; land management